Goal-Directed Fluid Therapy in Sepsis and Septic Shock: A Review of Current Therapeutic Strategies and Outcomes - Dobrucki, Maciej; Kuc, Katarzyna Jolanta; Brzezicki, Krzysztof; Zegadło, Katarzyna; Cieciora, Mateusz; Cieciora, Aleksandra; Jakubiak, Patryk; Kawiorska, Małgorzata; Surowiec, Julia; Bełcikowska-Skowron, Wiktoria Ruta (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Sepsis induces profound microvascular derangements, making prompt fluid resuscitation a management cornerstone. Historically guided by Early Goal-Directed Therapy (EGDT), landmark trials have refuted EGDT's rigidity, driving a shift toward individualized hemodynamics. The purpose of this review is to systematically evaluate goal-directed fluid therapy in septic shock, contrasting fluid composition, timing, and volume dosing to delineate clinical strategies that optimize survival. Description of the state of knowledge: Guidelines recommend crystalloids as first-line therapy and restrict synthetic colloids due to severe acute kidney injury (AKI) risks. Balanced crystalloids demonstrate marginal or comparable efficacy in reducing mortality rates relative to normal saline, the administration of which is often associated with the development of hyperchloremic metabolic acidosis. Hyperoncotic albumin appears to mitigate the risk of renal injury. The 30 mL/kg fluid mandate faces scrutiny, as non-individualized dosing may increase the risk of severe fluid overload. Current management utilizes the ROSE framework, favoring restrictive strategies and de-escalation. Obese patients require Ideal Body Weight dosing to prevent miscalculations. Summary: Meticulous fluid stewardship is essential to mitigate organ failure and maximize survival. Dynamic physiological indices outperform static parameters in predicting fluid responsiveness. Integrating personalized targets like capillary refill time normalization improves clinical outcomes. Individualized resuscitation appears to mitigate pathological venous congestion, which is often associated with improved long-term prognostic benefits.